2004
DOI: 10.1093/toxsci/kfh205
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Stimulation by Mycoplasma fermentans Synergistically Amplifies IL-6 Release by Human Lung Fibroblasts in Response to Residual Oil Fly Ash (ROFA) and Nickel

Abstract: Mycoplasma (MP), such as the species M. fermentans, possess remarkable immunoregulatory properties and can potentially establish chronic latent infections with little signs of disease. Atmospheric particulate matter (PM) is a complex and diverse component of air pollution associated with adverse health effects. We hypothesized that MP modulate the cellular responses induced by chemical stresses such as residual oil fly ash (ROFA), a type of PM rich in transition metals. We assessed the release of interleukin-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 58 publications
3
25
0
2
Order By: Relevance
“…Thus the most significant effect of mycoplasma in vivo may be fully realized only in the presence of other injurious or stressful stimuli. We have recently reported similar synergistic interactions between M. fermentans and metal-containing atmospheric particulate matter (17). It should be noted that not all HLF-derived cytokines were equally potentiated by M. fermentans.…”
Section: Discussionsupporting
confidence: 57%
“…Thus the most significant effect of mycoplasma in vivo may be fully realized only in the presence of other injurious or stressful stimuli. We have recently reported similar synergistic interactions between M. fermentans and metal-containing atmospheric particulate matter (17). It should be noted that not all HLF-derived cytokines were equally potentiated by M. fermentans.…”
Section: Discussionsupporting
confidence: 57%
“…Ni is a major component of ambient air particulate matter (1,35) that is associated with inappropriate immune responses (35,36), airway hyperresponsiveness (7,37), and increased cardiopulmonary disease (1). Mechanisms of action for inhaled Ni that are independent of its antigenicity remain poorly defined.…”
Section: Discussionmentioning
confidence: 99%
“…This is further confirmed by investigations that attribute different levels of toxicity to particles from different sources (Laden et al, 2000; Mar et al, 2000; Zhou et al (2011)). Toxicological studies have demonstrated the toxic potential of many individual PM components including sulfate, zinc, nickel and lead (Chuang et al, 2007; Gao et al, 2004; Lippmann et al, 2006; O’Neill et al, 2005). …”
Section: Introductionmentioning
confidence: 99%